The Development of Cardiac Surgery in an Emerging Country: A Completed Project - Velebit, Vladimir (Texas Heart Institute, 2008)
The necessity to develop cardiac surgery centers in the emerging world is widely accepted. Numerous groups and organizations from the developed world are involved in such work; however, the best method in which to develop a sustainable center in the emerging world is still debated. Herein, we present an approach that we have used in several such projects, which involves regular and frequent instructional visits with progressive reduction of our instructional support. Data to support our approach are presented.